Hubungan Tingkat Stres Akademik dan Kejadian Gastroesophageal Reflux Disease (GERD) pada Mahasiswa S1 Program Studi Kedokteran, Fakultas Kedokteran Universitas Ahmad Dahlan: Hasil Penelitian - Nirwani, Rr Syifa Aurora; Arifin, Zainul; Laariya, Tira Alfiani (PT Kalbe Farma Tbk., 2025)
Introduction: Gastroesophageal reflux disease (GERD) is a digestive system disorder characterized by recurrent reflux of stomach contents into the esophagus, leading to symptoms or complications. Academic stress is one of the risk factors for GERD. This research aims to determine the relationship between academic stress levels and the incidence of GERD among undergraduate students in the Medical Study Program, Faculty of Medicine, Ahmad Dahlan University. Methods: This study uses a quantitative observational analytical research method with a cross-sectional approach, employing total sampling based on inclusion and exclusion criteria. GERD is measured using the GERD-Q, and stress levels are assessed with the MSSQ questionnaire. Results: GERD was suffered by 26 respondents (14.8%), the majority were female. The majority of respondents, 85 in total (48.3%) experienced moderate stress; academic stress was the most common cause. The results of the chi-square analysis test between the level of academic stress and the incidence of GERD obtained a p-value of 0.052 (p>0.05). Conclusion: There is no significant relationship between academic stress levels and the incidence of GERD among undergraduates in the Medical Study Program at Ahmad Dahlan University Faculty of Medicine.